2020
DOI: 10.1073/pnas.2009316117
|View full text |Cite
|
Sign up to set email alerts
|

Direct readout of heterochromatic H3K9me3 regulates DNMT1-mediated maintenance DNA methylation

Abstract: In mammals, repressive histone modifications such as trimethylation of histone H3 Lys9 (H3K9me3), frequently coexist with DNA methylation, producing a more stable and silenced chromatin state. However, it remains elusive how these epigenetic modifications crosstalk. Here, through structural and biochemical characterizations, we identified the replication foci targeting sequence (RFTS) domain of maintenance DNA methyltransferase DNMT1, a module known to bind the ubiquitylated H3 (H3Ub), as a specific reader for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 62 publications
(74 reference statements)
7
76
0
Order By: Relevance
“…The BAH1–H4K20me3 binding-mediated allosteric activation of DNMT1 is reminiscent of the previously reported RFTS–H3K9me3Ub2 readout 29 . We therefore asked how the BAH1–H4K20me3 and RFTS–H3K9me3Ub2 interactions crosstalk.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…The BAH1–H4K20me3 binding-mediated allosteric activation of DNMT1 is reminiscent of the previously reported RFTS–H3K9me3Ub2 readout 29 . We therefore asked how the BAH1–H4K20me3 and RFTS–H3K9me3Ub2 interactions crosstalk.…”
Section: Resultssupporting
confidence: 68%
“…For instance, the DNMT1 RFTS domain (DNMT1 RFTS ) recognizes ubiquitinated histone H3 (H3Ub) 22 25 and PCNA-associated factor 15 (PAF15) 26 , 27 during S phase, which leads to cell cycle-specific chromatin targeting and enzymatic stimulation of DNMT1 23 , 26 , 28 . Our recent study further demonstrated that DNMT1 RFTS also directly recognizes H3K9me3, thereby reinforcing the DNMT1 RFTS -H3Ub readout for the DNA methylation maintenance at heterochromatic regions 29 . Likewise, the DNMT1 CXXC domain specifically recognizes unmodified CpG DNA to control DNMT1-mediated de novo DNA methylation 15 , 30 .…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…This intriguing new finding may help to explain our findings as well as those of the aforementioned studies. Our studies and these above-referenced findings also call into question a recent report implicating H3K9me3 recognition directly by DNMT1 as a mechanism that contributes to its DNA methylation maintenance function [50].…”
Section: Discussionsupporting
confidence: 52%